NETosis and associated host DNA orchestrate rhinovirus-induced type 2 allergic asthma exacerbation - Toussaint,M; Swieboda,D; Guedan,A; Jackson,DJ; Tsourouktsoglou,D; Ching,YM; Radermeker,C; Makrinioti,H; Aniescenko,J; Edwards,ME; Solari,R; Farnir,F; et al. (Nature Medicine, 2017)
Respiratory viral infections represent the most common cause of allergic asthma exacerbations. Amplification of type 2 immunity is strongly implicated in asthma exacerbation, but how virus infection boosts type 2 responses during exacerbation is poorly understood. We report a significant correlation between release of host double stranded DNA (dsDNA) following rhinovirus infection and exacerbation of type 2 allergic inflammation and disease severity in patients. In a mouse model, we show that rhinovirus infection triggers neutrophil extracellular traps (NETs) formation and host dsDNA release. We further demonstrate that inhibiting NETosis by blocking neutrophil elastase or degrading NETs with DNase protects mice from type 2 allergic asthma exacerbations. Furthermore, injection of host dsDNA alone is sufficient to recapitulate many features of rhinovirus-induced type 2 immune responses and asthma pathology. Thus, NETosis and host dsDNA contribute to exacerbation pathogenesis and may represent potential targets for novel treatments of rhinovirus-induced asthma exacerbations.